PERAN PSIKOLOGI AGAMA DALAM PENGUATAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM - Musriaparto Musriaparto (Koordinator Perguruan Tinggi Agama Islam (KOPERTAIS) Wilayah V Aceh, 2022)
In an effort to create people who know, live, believe, and practice religious teachings completely, so important to know that Islamic Religious Education cannot be separated from the touch of psychological aspects, especially the Psychology of Religion. Through the Psychology of Religion, it is hoped that the material for Islamic Religious Education has a psychological-critical element to better understand the religious phenomena related to the substance of Islamic Religious Education. Through the comparative approach, this study found that the Psychology of Religion played a role in strengthening the values of Islamic Religious Education. Some of these roles are understanding the stages of the religious soul of a student in order to adjust the presentation of the material, anticipating the occurrence of apostasy through the study of the psychology of religious conversion, understanding the meaning of mental health and mental disorders from an Islamic perspective, and strengthening religious tolerance.AbstrakSebagai sebuah upaya dalam menciptakan insan yang mengenal, menghayati, mengimani, mengamalkan ajaran agama secara kaffah, maka pendidikan Agama Islam tidak lepas dari sentuhan aspek-aspek psikologis, khususnya Psikologi Agama. Melalui Psikologi Agama diharapkan materi Pendidikan Agama Islam memiliki unsur psikologi-kritis untuk semakin memahami fenomena keberagamaan yang terkait substansi Pendidikan Agama Islam. Dengan menggunakan studi komparasi, penelitian ini kemudian menemukan bahwa Psikologi Agama berperan dalam penguatan nilai-nilai Pendidikan Agama Islam. Beberapa diantara peran tersebut yaitu Memahami tahapan jiwa agama seorang peserta didik dalam rangka menyesuaikan sajian materi, mengantisipasi terjadinya pemurtadan melalui kajian psikologi konversi agama, memahami makna kesehatan jiwa dan gangguan kejiwaan perspektif agama Islam dan penguatan toleransi beragama.